INTERCONNECTION OF THE ECONOMIC GROWTH CONCEPTS WITH INTERNATIONAL TECHNOLOGY TRANSFER - Когут, Мар’яна (Modern engineering and innovative technologies, 2023)
This article summarizes and systematizes the theoretical approaches of representatives of economic science to international technology transfer and economic growth. The evolution and defining provisions of the main theories of economic growth are analyzed